ANALISIS FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI EKONOMI RUMAH TANGGA PETANI PADI SAWAH DI KECAMATAN KUOK KABUPATEN KAMPAR - Elpi Evi; Djaimi Bakce; Jum’atri Yusri Yusri (DINAMIKA PERTANIAN, 2017)
The purpose of the research for analyzing determination factors that affect household economic of farmers against the production, allocation of work time, incomes, and expenses of field paddy household in the subdistrict of Kuok, district of Kampar. The analysis model used is the simultaneous equivalent model with Two-Stage Least Square (2SLS) method. The result of research concludes that: firstly, determination factors which affect production are harvest area and a total of allocation of working time in farming but there is no responsive variable. Secondly, the determining factors that affect the allocation of working time are the income in farming, allocation of out working in farming, labor force, income non-paddy farming, allocation of working time in farming, however only production variable which is responsive. Thirdly, determination factors that affect income non-paddy farming are allocation of non-working time, labor force, farmer’s age, and the experiences of farmer however, there is no responsive variable. Fourthly, determination factors that affect consumption are total of farmer’s income and the number of a household member, investment of education and savings, but only income total of the farmer is responsive can affect consumption.